KAJIAN ALAT BANTU PENDARATAN LOCALIZER BAGI KESELAMATAN PENERBANGAN DI PERUSAHAAN UMUM LEMBAGA PENYELENGGARA PELAYANAN NAVIGASI PENERBANGAN INDONESIA (PERUM LPPNPI) DISTRIK BATAM - Endang Sugih Arti.; Erwin Kurniadi; Badra R (Langit Biru: Jurnal Ilmiah Aviasi, 2016)
The aim of this research to know Localizer already standardized and whether the impact for aviation safety arising when localizer not working. This research was conducted at Perum LPPNPI Distrik Batam. Research methods used is descriptive and data collection methods are documentation, field observations, interviews and library studies.